The effects of Tripterygium wilfordii Hook F on renal outcomes in type 2 diabetic kidney disease patients with severe proteinuria: a single-center cohort study - Yaqi Cheng; Yuhao Liu; Liling Lin; Danni Li; Liying Peng; Ke Zheng; Jianling Tao; Mingxi Li (Renal Failure)
Aim Tripterygium wilfordii Hook F (TwHF) has been shown to substantially reduce proteinuria in patients with diabetic kidney disease (DKD); however, the effect of TwHF on renal outcomes in DKD remains unknown. Accordingly, we aimed to establish the effects of TwHF on renal outcomes in patients with DKD.Methods Overall, 124 patients with DKD, induced by type 2 diabetes mellitus, with 24-h proteinuria > 2 g, and an estimated glomerular filtration rate > 30 mL/min/1.73 m2 were retrospectively investigated. The renal outcomes were defined as doubling serum creatinine levels or end-stage kidney disease. Kaplan-Meier curves and Cox regression analyses were performed to analyze prognostic factors for renal outcomes.Results By the end of the follow-up, renal outcomes were observed in 23 and 11 patients in the non-TwHF and TwHF groups, respectively (p = 0.006). TwHF significantly reduced the risk of renal outcomes (adjusted hazard ratio [HR] 0.271, 95% confidence interval [CI] 0.111–0.660, p = 0.004) in patients with chronic kidney disease (CKD) G3 (adjusted HR 0.274, 95%CI 0.081–0.932, p = 0.039). Based on the Kaplan-Meier analysis, 1- and 3-year proportions of patients without renal outcomes were significantly lower in the non-TwHF group than those in the TwHF group (92.8% vs. 95.5% and 47.2% vs. 76.8%, respectively; p = 0.0018).Conclusion In DKD patients with severe proteinuria, TwHF could prevent DKD progression, especially in patients with CKD G3. A randomized clinical trial is needed to elucidate the benefits of TwHF on renal outcomes in patients with DKD.